2017
DOI: 10.3171/2016.7.peds1651
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy surgery in patients with autism

Abstract: OBJECTIVE The purpose of this study was to report outcomes of epilepsy surgery in 56 consecutive patients with autism spectrum disorder. METHODS Medical records of 56 consecutive patients with autism who underwent epilepsy surgery were reviewed with regard to clinical characteristics, surgical management, postoperative seizure control, and behavioral changes. RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…6 Our group has previously shown the feasibility and safety of epilepsy surgery in children with ASD, emphasizing the potential for better seizure control and associated gains in cognition with reductions in violent behavior. 12 Not surprisingly, children with ASD and MRI-negative epilepsy, similar to the two presented here, appeared to have worse outcomes than their lesional counterparts after an irreversible ablative treatment. 12 We chose a modulatory approach in the current patients for several reasons.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…6 Our group has previously shown the feasibility and safety of epilepsy surgery in children with ASD, emphasizing the potential for better seizure control and associated gains in cognition with reductions in violent behavior. 12 Not surprisingly, children with ASD and MRI-negative epilepsy, similar to the two presented here, appeared to have worse outcomes than their lesional counterparts after an irreversible ablative treatment. 12 We chose a modulatory approach in the current patients for several reasons.…”
Section: Discussionsupporting
confidence: 62%
“…12 Not surprisingly, children with ASD and MRI-negative epilepsy, similar to the two presented here, appeared to have worse outcomes than their lesional counterparts after an irreversible ablative treatment. 12 We chose a modulatory approach in the current patients for several reasons. Novel treatments such as RNS have added to our armamentarium in treating epilepsy in adults.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Overall, 1742 patients were included from 58 unique studies (Table 1). 1,3–10, 1821, 2326, 29, 3234, 36, 37, 3947, 4957,5962, 66, 6976, 7982 All studies were retrospective or prospective case series, and no controlled studies were identified. Overall, the rates of complete seizure freedom and freedom from drop attacks were 18.8% and 55.3%, respectively, at last follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…164 For those individuals who have failed prior psychopharmacology attempts, and those who exhibit unusual and challenging behaviours-for example, sudden and unprovoked outbursts of aggression, irritability, crying, screaming or self-harming, unusual facial and body movements and postures, staring spells, covering of ears-an EEG could be helpful for differentiating between seizures and non-epileptic paroxysmal behaviours. 165,166 Metabolic Irregularities, Acquired Mitochondrial Dysfunction and Oxidative Stress in ASD Children and adults with ASD are at significantly greater risk for weight issues and obesity than the general population. 167 Compared with those presenting with milder impairments, individuals with severe ASD also show an increased likelihood of obesity alongside various other metabolic disorders including hypertension, diabetes and dyslipidemia.…”
Section: Seizure Disorders and Epilepsy In Asdmentioning
confidence: 99%